2021
DOI: 10.1039/d1ta03375a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-supported catalysts with atomically dispersed metal sites for oxygen electroreduction: present and future perspectives

Abstract: Carbon-supported catalysts with atomically dispersed metal sites, also known as “single-atom catalysts (SACs)”, have attracted enormous attention for oxygen reduction reaction (ORR) due to their theoretical maximal atom utilization and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 146 publications
1
12
0
Order By: Relevance
“…76–78 Among them, the dopant atoms used in the reported work mainly include N, S, P, B, O, I, Cl and so on. 9,79–81 As a highly electronegative atom with a lone pair of electrons, N is incorporated into carbon materials to form M–N x structure catalysts. This strategy has been extensively studied as described in Section 2.1.…”
Section: Structure Classificationmentioning
confidence: 99%
“…76–78 Among them, the dopant atoms used in the reported work mainly include N, S, P, B, O, I, Cl and so on. 9,79–81 As a highly electronegative atom with a lone pair of electrons, N is incorporated into carbon materials to form M–N x structure catalysts. This strategy has been extensively studied as described in Section 2.1.…”
Section: Structure Classificationmentioning
confidence: 99%
“…12,13 Therefore, increasing the density of FeN x sites is an efficient method to improve catalytic activity. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Therefore, increasing the density of FeN x sites is an efficient method to improve catalytic activity. 14,15 To date, the content of Fe atoms in most Fe-N-C catalysts has reached more than 2.0 wt% by optimization of the combinations of precursor and the temperature of carbonization. 16 However, a lot of FeN x sites are located and buried within the carbon matrix, which is not involved in the ORR process.…”
Section: Introductionmentioning
confidence: 99%
“…[31,40] Our previous study has demonstrated that a catalyst with isolated single Fe atoms of Fe-N 4 coordination anchored on N-doped porous carbon (Fe SA/NPCs) possesses superior catalytic activity on oxygen reduction reaction (ORR). [41,42] Furthermore, other studies have also shown that anchoring single atoms of transition metals on N-doped carbon substrates can dramatically improve the degradation of bisphenol A (BPA). [43][44][45] Hence, it is envisioned that SACs of transition metals on carbonaceous substrates can also function in Fenton-like process, which can be used in pollutant degradation and sterilization.…”
Section: Introductionmentioning
confidence: 99%